A17, the First Sequenced Strain of Lactococcus lactis subsp. cremoris with Potential Immunomodulatory Functions - Yang, Chih-Hsien (Genome Announc, 2015)
Lactococcus lactis subsp. cremoris A17, isolated from Taiwan fermented cabbage, is the first sequenced strain of L. lactis subsp. cremoris with immunomodulatory activity and antiallergic functions. The resulting A17 draft genome contains 2,679,936 bp and indicates that A17 is a potential exopolysaccharide-producing strain without any known virulence gene.